Association between serious psychological distress and health care use and expenditures by cancer history. Issue 4 (23rd October 2014) - Han, Xuesong; Lin, Chun Chieh; Li, Chunyu; de Moor, Janet S.; Rodriguez, Juan L.; Kent, Erin E.; Forsythe, Laura P.
Abstract : BACKGROUND: Serious psychological distress (SPD) is associated with adverse health outcomes such as poor quality of life and shorter survival in cancer survivors, but to the authors' knowledge, the relationship between SPD and health care use and medical expenditures is not clear. METHODS: A total of 4326 cancer survivors and 57, 109 noncancer participants were identified from the 2008 through 2010 Medical Expenditure Panel Survey, a nationwide population‐based survey, and their psychological distress was assessed with the 6‐item Kessler Psychological Distress Scale (SPD defined by a score ≥13). The association between SPD and use and medical expenditures of various types of health care (office‐based, outpatient, hospital inpatient, emergency department, dental, and prescriptions) was examined using a 2‐part modeling approach that adjusted for demographic, personal, and comorbidity factors. The marginal effects of SPD on health care use and expenditures were calculated for cancer survivors and were compared with those of noncancer participants. RESULTS: The weighted prevalence of SPD in cancer survivors was 8.2% compared with 4.8% in the noncancer participants. SPD was significantly associated with higher use of all care types except dental care in cancer survivors. Cancer survivors with SPD spent 4431 (95% confidence interval, 3419‐5443) more than survivors without SPD on medical services each year, whereas this extra expenditure associated with SPD for participants without cancer was 2685 (95% confidence interval, 2099‐3271). CONCLUSIONS: In a national representative sample of cancer survivors, SPD was found to be associated with higher health care use and medical expenditures. Distress screening and psychosocial care in cancer survivors may help reduce the economic burden of cancer in the United States. Cancer 2015;121:614–622. © 2014 American Cancer Society . Abstract : Serious psychological distress is reported to be associated with adverse health outcomes such as poor quality of life and shorter survival in cancer survivors. In a national representative sample of cancer survivors, serious psychological distress was found to be associated with higher health care use and medical expenditures.